FkbN and Tcs7 are pathway-specific regulators of the FK506 biosynthetic gene cluster in Streptomyces tsukubaensis L19. (1st December 2016) - Zhang, Xiao-Sheng; Luo, Hong-Dou; Tao, Yang; Wang, Yue-Yue; Jiang, Xin-Hang; Jiang, Hui; Li, Yong-Quan
Abstract: FK506 (tacrolimus), which is produced by many Streptomyces strains, is clinically used as an immunosuppressive agent and for treatment of inflammatory skin diseases. Here, we identified that the FK506 biosynthetic gene cluster in an industrial FK506-producing strain Streptomyces tsukubaensis L19 is organized as eight transcription units. Two pathway-specific regulators, FkbN and Tcs7, involved in FK506 biosynthesis from S. tsukubaensis L19 were characterized in vivo and in vitro. FkbN activates the transcription of six transcription units in FK506 biosynthetic gene cluster, and Tcs7 activates the transcription of fkbN . In addition, the DNA-binding specificity of FkbN was determined. Finally, a high FK506-producing strain was constructed by overexpression of both fkbN and tcs7 in S. tsukubaensis L19, which improved FK506 production by 89 % compared to the parental strain.